The developmental factor TBX3 engages with the Wnt/β-catenin transcriptional complex in colorectal cancer to regulate metastasis genes - Amaia Jauregi-Miguel; Simon Söderholm; Tamina Weiss; Anna Nordin; Valeria Ghezzi; Salome M. Brütsch; Pierfrancesco Pagella; Yorick van de Grift; Gianluca Zambanini; Jacopo Ulisse; Alessandro Mattia; Ruslan Deviatiiarov; et al. (Proceedings of the National Academy of Sciences, 2025)
Wnt signaling orchestrates gene expression in a plethora of processes during development and adult cell homeostasis via the action of nuclear β-catenin. Yet, little is known about how β-catenin generates context-specific transcriptional outcomes. Understanding this will reveal how aberrant Wnt/β-catenin signaling causes neoplasia specifically of the colorectal epithelium. We have previously identified the transcription factor TBX3 as a tissue-specific component of the Wnt/β-catenin nuclear complex during mouse forelimb development. In this study, we show that TBX3 is functionally active in human colorectal cancer (CRC). Here, genome-wide binding and transcriptomics analyses reveal that TBX3 regulates cancer metastasis genes in cooperation with Wnt/β-catenin. Proteomics proximity labeling performed across Wnt pathway activation shows that TBX3 engages with several transcription factors and chromatin remodeling complexes found at Wnt responsive elements (WRE). Protein sequence and structure analysis of TBX3 revealed short motifs, including an exposed Asn-Pro-Phe (NPF), that mediate these interactions. Deletion of these motifs abrogates TBX3’s proximity to its protein partners and its ability to enhance the Wnt-dependent transcription. TBX3 emerges as a key modulator of the oncogenic activity of Wnt/β-catenin in CRC, and its mechanism of action exposes protein-interaction surfaces as putative druggable targets.